1996
DOI: 10.1097/00006123-199605000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the History and Survival of Patients with, Supratentorial Low-grade Astrocytomas

Abstract: Data from 55 consecutive patients with low-grade astrocytomas treated between 1982 and 1990 were analyzed to determine specific outcome factors, including time to recurrence, incidence of anaplastic transformation, and survival. Gender, type of symptoms, contrast enhancement, and timing of radiation therapy were not significant in determining outcome. Patients who had symptoms for > 2 years and underwent gross-total resection of the tumor, with age as a continuous variable, were associated with significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
114
1
10

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(128 citation statements)
references
References 30 publications
3
114
1
10
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Current primary treatment options include surgical resection and/or radiotherapy, although definitive evidence for an optimal treatment remains elusive. Advances in molecular epidemiology indicate that certain histologic subtypes of low-grade gliomas, such as oligodendrogliomas, may have varied response to chemother- apeutic agents based on chromosomal changes, including loss of chromosome 1p and/or 19q, and, hence, may have improved survival with use of these agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Current primary treatment options include surgical resection and/or radiotherapy, although definitive evidence for an optimal treatment remains elusive. Advances in molecular epidemiology indicate that certain histologic subtypes of low-grade gliomas, such as oligodendrogliomas, may have varied response to chemother- apeutic agents based on chromosomal changes, including loss of chromosome 1p and/or 19q, and, hence, may have improved survival with use of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many projects [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] that have examined the association between both the use and the extent of surgical resection with outcomes for neurosurgical patients who are diagnosed with low-grade gliomas, 3 the relation remains unclear. In addition, although previous studies have examined the role of intraoperative magnetic resonance imaging (MRI) in tumor volume measurement, 18,20 the reports that exist generally are relatively small in size, present estimates that were not adjusted for age and/or histology, vary by study patient composition, or present study results in nonstandard statistical format.…”
mentioning
confidence: 99%
“…It has been assessed that 49 -85% of low-grade astrocytomas undergo transformation to a higher grade at some point along the course. [3][4][5] Malignant transformation occurs also in low-grade oligodendrogliomas. 6 Therefore, it is reasonable to assume that an early malignant transformation is responsible for the short survival in some of these patients.…”
mentioning
confidence: 99%
“…[21,26,40,49,50,56,61,66,67] The histological modification at recurrence can be attributed either to occurrence of malignant transformation or to the expression of an aggressive component in the original tumor that was missed on the tissue specimen submitted for pathological review. [77] The benefit of surgery seems to result from a significant decrease in the risk of recurrence in patients who underwent aggressive surgical treatment, compared to those receiving anything less than gross-total resection.…”
mentioning
confidence: 99%
“…[77] The benefit of surgery seems to result from a significant decrease in the risk of recurrence in patients who underwent aggressive surgical treatment, compared to those receiving anything less than gross-total resection. [61,62] Berger, et al, [2] have reported on the association between extent of resection and recurrence, using a univariate analysis, in a series of 53 patients with heterogeneous tumor types (19 astrocytoma, 18 oligodendroglioma, and 16 mixed oligoastrocytoma). Analysis of results in this study suggested that both tumor size at presentation and after resection may influence the natural history of low-grade gliomas.…”
mentioning
confidence: 99%